Sistem Manajemen Program Kelas Khusus Olahraga di Sekolah Menengah Pertama - Annifa’ari, Andi Adelia Nabila; Rosalina Noor, Triana (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to describe how the management system of the special sports class program (KKO) at SMP PGRI 9 Sidoarjo. KKO is a place to serve students who have talent or potential in the field of sports. This research uses a qualitative case study method with data collection methods using interviews, observations and documents. The research subjects included four people, namely the principal, sports teacher, vice principal of curriculum and coach, who were determined based on purposive techniques. After the data is collected, data analysis is carried out through the process of data reduction, data presentation and conclusion drawing by referring to the management stages. The results of this study illustrate that the KKO program management system at SMP PGRI 9 Sidoarjo has been running quite well through the stages of planning, organizing, implementing and supervising which are quite mature. At the planning stage, the school formulates the purpose of opening this special sports class by referring to the school's vision and mission through the preparation of annual programs, budget planning and preparation of infrastructure needs. At the implementation stage, the school implements a structured lesson schedule and training schedule. Supervision is carried out by coordinating regularly once a week to evaluate student achievements both academically and sports achievements. The results of this study can be used as evaluation material and inspiration for policy makers in developing policies that support talent development programs through effective and integrated management